Implementation of the FLORET UTE sequence for lung imaging. Issue 3 (13th May 2019) - Willmering, Matthew M.; Robison, Ryan K.; Wang, Hui; Pipe, James G.; Woods, Jason C.
Abstract : Purpose: Magnetic resonance imaging of lungs is inherently challenging, but it has become more common with the use of UTE sequences and their relative insensitivity to motion. Spiral UTE sequences have been touted recently as having greater k‐space sampling efficiencies than radial UTE, but few are designed for the shorter T2 * of the lung. In this study, FLORET (Fermat looped, orthogonally encoded trajectories), a recently developed spiral 3D‐UTE sequence designed for the short T2 * species, was implemented in human lungs for the first time and the images were compared with traditional radial UTE images. Methods: The FLORET sequence was implemented with parameters optimized for lung imaging on healthy and diseased (cystic fibrosis) subjects. On healthy subjects, radial UTE images (3D‐radial and 2D‐radial with phase encoding) were acquired for comparison to FLORET. Various metrics including SNR, vasculature contrast, diaphragm sharpness, and parenchymal density ratios were acquired and compared among the separate UTE sequences. Results: The FLORET sequence performed similarly to traditional radial UTE methods with a much shorter total scan time for fully sampled images (FLORET: 1 minute 55 seconds, 3D‐radial: 3 minutes 25 seconds, 2D‐radial with phase encoding: 7 minutes 22 seconds). Additionally, the FLORET image obtained on the cystic fibrosis subject resulted in the observation of cystic fibrosis lung pathology similar or superior to that of the other UTE‐MRI techniques. Conclusion: The FLORET sequence allows for faster acquisition of high diagnostic‐quality lung images and its short T2 * components without sacrificing SNR, image quality, or tissue/disease quantification.